Nanostructured LB films developed from poly(p-acryloylaminophenylmethylphosphonic) acid. (22nd July 2016) - Lazo-Jiménez, Rosa E.; Chávez-Carvayar, José A.; Herrera-González, Ana M.; Islas-Pérez, Valentin; Carreón-Castro, María P.
ABSTRACT: In this paper, the formation of Langmuir-Blodgett films of poly( p -acryloylaminophenylmethylphosphonic) acid polymers, with general formula (C10 H12 NPO4 )n are reported. The Langmuir-Blodgett (LB) technique was used for building ordered nanostructures in molecular assemblies of these polymers, which were able to form stable films. At the air-water interface, these polymers (with low and high molecular weight) formed Langmuir (L) monolayers, which were characterized by surface pressure versus molecular area ( π - A ) isotherms and Brewster´s Angle Microscopy (BAM). Using the LB method, molecular mono and multilayer films of these polymers were prepared and transferred onto glass substrates forming Z-type multilayers, with a transfer ratio close to unity. These LB films were characterized by Atomic Force Microscopy (AFM).